(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
GENRES OF LITERATURE—DRAMA The word drama is gotten from the Greek word “Dran” which means to do or act. Drama as a genre of literature possesses a major feature which is action, irrespective of whether it is on a built stage or on a village pathway as in the case of village festivals or dances. And this becomes a unifying factor for all dramatic.